2004
DOI: 10.1016/j.ejcts.2004.02.013
|View full text |Cite
|
Sign up to set email alerts
|

OPCAB versus early mortality and morbidity: an issue between clinical relevance and statistical significance☆

Abstract: The observed 20% reduction of mortality, 60% reduction of stroke and 20% reduction of dialysis were partly neutralized by the adjusting methods and demand, at least, larger datasets to obtain statistical significance. Subdatasets with fewer patients but higher risk identified risk-reducing effects for stroke. Hospital stay was shortened by the OPCAB approach. The interactions between risk, number of patients and the risk-reducing effect are the cornerstones of evidence generation for the OPCAB approach. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 21 publications
1
25
1
4
Order By: Relevance
“…La cirugía coronaria sin CEC reduce, aunque no suprime, los valores circulantes de mediadores inflamatorios 74 , y la eliminación del pinzamiento aórtico reduce el sufrimiento miocárdico. Aunque los resultados clínicos no han alcanzado aún evidencia clase I, los resultados de series amplias observacionales indican el beneficio de esta técnica en términos de supervivencia a corto y largo plazo, principalmente en pacientes con disfunción ventricular, diabéticos y ancianos [79][80][81] , incidencia de infarto de miocardio y accidente cerebrovascular 82 , y reducción de la incidencia de fibrilación auricular postoperatoria 83 . La cirugía coronaria con injertos arteriales sin CEC asociada a anestesia epidural torácica y fast track representa actualmente el patrón oro.…”
Section: Cirugía Coronaria Menos Invasivaunclassified
“…La cirugía coronaria sin CEC reduce, aunque no suprime, los valores circulantes de mediadores inflamatorios 74 , y la eliminación del pinzamiento aórtico reduce el sufrimiento miocárdico. Aunque los resultados clínicos no han alcanzado aún evidencia clase I, los resultados de series amplias observacionales indican el beneficio de esta técnica en términos de supervivencia a corto y largo plazo, principalmente en pacientes con disfunción ventricular, diabéticos y ancianos [79][80][81] , incidencia de infarto de miocardio y accidente cerebrovascular 82 , y reducción de la incidencia de fibrilación auricular postoperatoria 83 . La cirugía coronaria con injertos arteriales sin CEC asociada a anestesia epidural torácica y fast track representa actualmente el patrón oro.…”
Section: Cirugía Coronaria Menos Invasivaunclassified
“…35 The advantages of OPCAB have been observed for high-risk cases, 29,32 and it is believed that this trial targeting low-risk male subjects was unable to demonstrate the superiority of OPCAB. Sergeant et al reported a significant reduction in the risk of stroke in highrisk patients, 36 and the OPCAB technique might be associated with a reduced incidence of stroke, particularly in elderly patients. 37 Nishiyama et al 38 conducted a study of stroke, based on the CREDO-Kyoto database.…”
Section: Opcab Vs On-pump Cabgmentioning
confidence: 99%
“…An alternative approach is to adopt the technique wholesale after a period of intense training or "re-engineering" as pursued by Sergeant and colleagues. 16 Mack and colleagues 17 recently reported a large retrospective study encompassing four centers over a 3-year period. The study examined 17,401 isolated coronary artery bypass procedures, of which 7,283 (41.9%) were off-pump and 10,118 (58.1%) were on-pump.…”
Section: Clinical Outcomementioning
confidence: 99%
“…Sergeant and colleagues 16 analyzed a consecutive series of 3,333 patients undergoing coronary artery surgery (1,593 on-pump and 1,740 off-pump). They found a trend towards a 60% reduction of stroke, which after risk adjustment, fell below the level of significance for the total population, but the benefit persisted for patients with severe stenosis of the internal carotid artery.…”
Section: Risk Of Cerebral Injurymentioning
confidence: 99%